Ittijahat Abi Dhu'ayb Al-Hudhali fi Qasidatihi Ar-Ritsa’ - Raissa Nofrina Halim; Zulkhairi Sofyan (Jurnal Adabiya, 2022)
This article aims to know Ittijahat of Abu Dhu’ayb Al-Hudhali in his poem of Ritsa’. Ittijahat in this study is a description of the poet's tendency to divide Ar-Ritsa', namely Nadb and Ta'ziyah. Ar-Ritsa 'is one of the various forms of Arabic poetry. To analyze the discussion problem, the author uses descriptive analysis method, because this method is very appropriate to find out the picture and state of a thing by describing it in as much detail as possible based on the facts found in the data in question. The results obtained are: In the beginning of the poem, he tends to mourn (Nadb) their five children. He describes in it that he does not stop crying and has trouble sleeping until he becomes weak emaciated due to the intensity of the grief, pain and worries that dominated in his pysche. As for the middle of the poem to the end, the poet turns to the consolation (Ta’ziyah) of his children’s death, as he reflects on the reality of life and death, the poet declares that death is inevitable for every human being that he must accept it and let it go, which the poet portrayed in the exciting narrative style. The story is divided into three stories: the zebra, the bull of the beast, and the two knights.